The representation of emotions in groups: the relative impact of social norms, positive-negative asymmetry and familiarity on the perception of emotions - Dario Paez (1996)
Research in several countries shows that people hold norms of emotion perception, so that socially desirable emotions are perceived as positive and moderate. Subjects also believe that positive and moderate emotions are dominant in their lives. Other research shows that increased familiarity with a social group allows a better differentiation among the members and the attributes of this group (e.g. wider variability of emotions). In the present study, we compare the relative impact of familiarity with pleasant and unpleasant groups and social norms on emotion perception. Subjects (N = 150) were to rate imagined family groups, families that they did not know well, and families that they knew very well, on perceived differentiation and variability of emotional episodes, extremity of emotional events, and global family evaluations. Results indicated that familiarity is weakly associated with perceived emotional variability in target families, and that, regardless of their familiarity with the family, subjects viewed unpleasant families as more negative, as less familiar, and as having a larger range of emotions than pleasant families. Results are discussed in terms of the idea that perception of emotions in groups depends more strongly on social norms than either on positive-negative asymmetry or on direct experience with their members.